Human profilin 1 is a negative regulator of CTL mediated cell‐killing and migration. Issue 9 (31st July 2017) - Schoppmeyer, Rouven; Zhao, Renping; Cheng, He; Hamed, Mohamed; Liu, Chen; Zhou, Xiao; Schwarz, Eva C.; Zhou, Yan; Knörck, Arne; Schwär, Gertrud; Ji, Shunrong; Liu, Liang; et al.
Abstract : Profilin 1 negatively regulates CTL‐mediated killing, CTL migration and lytic granule release. Profilin 1 tunes the duration and the symmetry of CTL protrusions. Profilin 1 is decreased in CTL from patients with pancreatic cancer, suggesting a role of profilin 1 on CTL functionality in a tumor‐related context. Abstract: The actin‐binding protein profilin1 (PFN1) plays a central role in actin dynamics, which is essential for cytotoxic T lymphocyte (CTL) functions. The functional role of PFN1 in CTLs, however still remains elusive. Here, we identify PFN1 as the only member of the profilin family expressed in primary human CD8 + T cells. Using in vitro assays, we find that PFN1 is a negative regulator of CTL‐mediated elimination of target cells. Furthermore, PFN1 is involved in activation‐induced lytic granule (LG) release, CTL migration and modulation of actin structures at the immunological synapse (IS). During CTL migration, PFN1 modulates the velocity, protrusion formation patterns and protrusion sustainability. In contrast, PFN1 does not significantly affect migration persistence and the rates of protrusion emergence and retraction. Under in vitro conditions mimicking a tumor microenvironment, we show that PFN1 downregulation promotes CTL invasion into a 3D matrix, without affecting the viability of CTLs in a hydrogen peroxide‐enriched microenvironment. Highlighting its potential relevance in cancer, we find that in pancreatic cancer patients, PFN1 expression is substantially decreased in peripheral CD8 + T cells. Taken together, we conclude that PFN1 is a negative regulator for CTL‐mediated cytotoxicity and may have an impact on CTL functionality in a tumor‐related context.